The role of epigenetics in pulmonary fibrosis: recent advances in mechanistic insights and therapeutic implications - Jingru Huang; Jianfeng Qin; Yuguang Zhu; Ao Shen (Frontiers in Molecular Biosciences)
Pulmonary fibrosis (PF) is a fatal disease characterized by progressive fibrosis of lung tissue, with a key pathological feature of excessive accumulation of extracellular matrix. PF occurs from complicated origins, while emerging findings have suggested the involvement of the environmental factors in the risk of PF through epigenetic regulation. This article will discuss how recent advances in epigenetic alterations of DNA methylation, RNA methylation, histone modifications, and non-coding RNAs contribute to PF development through molecular mechanisms and cellular processes, including fibroblast-to-myofibroblast transition (FMT), epithelial-to-mesenchymal transition (EMT), alveolar epithelial cell injury and immune cell interactions in the past 5 years.